Revision of the loach species Barbatula nuda (Bleeker 1865) (Pisces: Balitoridae) from North China, with a description of a new species from Inner Mongolia - Cao, Liang; Causse, Romain; Zhang, E (Zootaxa, 2012)
Variation in the currently recognized species, Barbatula nuda (Bleeker 1865), from North China was studied, and threedistinct species are identified: B. nuda, B. toni, and B. gibba sp. nov.. The name B. nuda is presently misapplied; this speciesis distinct from B. toni, a species widely distributed in Northeast China, and occurs only in the Liao-He basin of LiaoningProvince and the Tumen-Jiang basin of Jilin Province. The new species, B. gibba, is only found in Dali-Nur Lake in Inner Mongolia. Among Chinese Barbatula species, it is uniquely distinguished by the shape of the predorsal body.